(untitled) (Conference on English Language Teaching, 2023)
One increasingly common method to elicit beliefs and conceptualizations is metaphor analysis, whereby participants create metaphors for relevant activities/concepts and then actively engage with them. This study analyzed EFL teachers’ metaphors related to their professional identity (TPI). The participants were 13 EFL teachers who worked in the various educational institutions. Data were collected through the Metaphor Questionnaire about the concept of teacher’s professional identity and followed by semi-structured interview to explore the reason for using those metaphors. Content analysis was used in analyzing the responses turned in by the EFL teachers. On analysis, results revealed that EFL teachers use diverse metaphors that are related to their everyday lived experiences. On categorizing the metaphors, four themes emerged namely profession, animal, amusement park attraction and infrastructure. The most prominent metaphor in this study is profession. Lastly, the metaphors revealed that the EFL teachers had fair understanding about their professional identity. The implications of the findings for teacher education were discussed.